Reports of perceptual distortion of the face are common in patients with different types of chronic oro‐facial pain. (30th January 2016) - Dagsdóttir, L. K.; Skyt, I.; Vase, L.; Baad‐Hansen, L.; Castrillon, E.; Svensson, P.
Summary: Anecdotally, chronic oro‐facial pain patients may perceive the painful face area as 'swollen'. Because there are no clinical signs, these self‐reported 'illusions' may represent perceptual distortions and can be speculated to contribute to the maintenance of oro‐facial pain. This descriptive study investigated whether chronic oro‐facial pain patients experience perceptual distortions – a kind of body image disruption. Sixty patients were consecutively recruited to fill in questionnaires regarding i) pain experience, ii) self‐reports of perceptual distortion and iii) psychological condition. Perceptual distortions were examined in the total group and in three diagnostic subgroups: i) painful post‐traumatic trigeminal neuropathy (PPTN), ii) painful temporomandibular disorder (TMD) or iii) persistent idiopathic facial pain (PIFP). A large proportion of oro‐facial pain patients reported perceptual distortions of the face (55·0%). In the diagnostic subgroups, perceptual distortions were most pronounced in PPTN patients (81·5%) but with no significant group differences. In the total group of chronic oro‐facial pain patients, the present pain intensity explained 16·9% of the variance in magnitude of the perceptual distortions ( R 2 = 16·9, F (31) = 6·3, P = 0·017). This study demonstrates that many chronic oro‐facial pain patients may experience perceptual distortions. Future studies may clarify the mechanisms underlying perceptual distortions, which may point towards new complementary strategies for the management of chronic oro‐facial pain.